2005
DOI: 10.1016/j.drugalcdep.2004.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and tobacco use patterns among heterosexually and homosexually experienced California women

Abstract: Background-Mounting evidence suggests that lesbians and bisexual women may be at especially elevated risk for the harmful health effects of alcohol and tobacco use.Methods-We report findings from the California Women's Health Survey (1998)(1999)(2000), a large, annual statewide health surveillance survey of California women that in 1998 began to include questions assessing same-gender sexual behavior.Results-Overall, homosexually experienced women are more likely than exclusively heterosexually experienced wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
8
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(159 citation statements)
references
References 49 publications
7
139
8
5
Order By: Relevance
“…This result contrasts with other studies of alcohol consumption among LGB individuals, which have tended to document differences only among women (e.g., Burgard et al, 2005;. However, studies of LGB young adults have been cross-sectional and therefore might have obscured prospective differences in alcohol consumption between heterosexual and nonheterosexual men.…”
Section: Discussioncontrasting
confidence: 77%
“…This result contrasts with other studies of alcohol consumption among LGB individuals, which have tended to document differences only among women (e.g., Burgard et al, 2005;. However, studies of LGB young adults have been cross-sectional and therefore might have obscured prospective differences in alcohol consumption between heterosexual and nonheterosexual men.…”
Section: Discussioncontrasting
confidence: 77%
“…Epidemiological studies have shown higher prevalences of alcohol and drug disorders in some sexual minority populations (1-7). Similarly, the prevalence of some commonly occurring psychiatric disorders appears to be elevated within sexual minorities (3,8,9 ).…”
Section: Introductionmentioning
confidence: 99%
“…LGBT people are at elevated risk when it comes to mental health disorders and psychological morbidity (Burgard et al, 2005).…”
Section: Mental Health Research Has Demonstrated Thatmentioning
confidence: 99%
“…Considering the prevalence of mental health disorders among LGBT immigrants (Burgard et al, 2005;Ayala & Diaz, 2001;Cochran et al, 2007), the challenges, discussed above, related to access to and receipt of mental health services are concerning. Furthermore, untreated mental health disorders can have impacts on the physical and behavioural health of…”
Section: Somementioning
confidence: 99%